Taxes and women in the labour force in a Southern European country: the case of Portugal - Marques, Ana Cristina Lino (2021)
Abstract. On looking at the female labour supply in Europe, it is immediately noticed that there is a large variation among countries. One possible explanation for this fact is that different countries have different tax policies, leading to variations in incentive and costs. This has been investigated in papers such as that of Gustafsson (1992a,b) for countries such as Germany and Sweden. The same exercise has been performed by the present authors for a low-income, southern European country, Portugal, which has one of the highest rates of female participation (out of line with neighbouring countries). Female labour supply does not seem to be very sensitive to fiscal policies, as those policies have only a small influence on the take-home wage. This result appears to be independent of the fact that the female labour supply shows a higher elasticity to wages than that which has been reported for other countries. The present authors also show that Portuguese women contribute a much larger proportion of family earnings than do their counterparts in Sweden and Germany, and that the Portuguese fiscal system is rather neutral. Further studies with data from other countries are needed in order to shed more light on the issue of tax harmonization.